Introduction to special issue: Rail transit development in China and beyond - Mi Diao; Yingling Fan; Xueliang Zhang (Journal of Transport and Land Use)
Rail transit is widely considered an efficient and environment-friendly means to address the increasing demand for travel. In the past decades, the scale and speed of China's rail transit development has been unprecedented. By the end of 2017, a total of 165 urban rail lines including heavy rail and light rail were in operation in 34 cities in mainland China, with a total track length of 5,033 kilometers (km), and the vast majority of them were built after 2000 (China Association of Metros, 2017). At the intercity scale, China has built the largest high-speed rail (HSR) network in the world, with over 29,000 km HSR lines by the end of 2018 (Central Government of China, 2019). Efforts to develop rail transit are also observed in other cities in both developing and developed countries.